2020
DOI: 10.1101/2020.04.08.20057414
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A minimal and adaptive prediction strategy for critical resource planning in a pandemic

Abstract: Current epidemiological models can in principle model the temporal evolution of a pandemic. However, any such model will rely on parameters that are unknown, which in practice are estimated using stochastic and poorly measured quantities. As a result, an early prediction of the long-term evolution of a pandemic will quickly lose relevance, while a late model will be too late to be useful for disaster management. Unless a model is designed to be adaptive, it is bound either to lose relevance over time, or lose … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…However, by May 18, many nations are close to the flattening of their epidemic curves. Besides the above results, Prakash et al [31] reported a linear growth of I(t) after early exponential growth.…”
Section: Introductionmentioning
confidence: 74%
“…However, by May 18, many nations are close to the flattening of their epidemic curves. Besides the above results, Prakash et al [31] reported a linear growth of I(t) after early exponential growth.…”
Section: Introductionmentioning
confidence: 74%
“…We thus provide a mechanistic model for short term prediction of COVID-19 epidemic data. Compared to empirical measures 14,16,18 this method recreates data using parameters that are intuitive and directly related to operation on the field. While similar to other mechanistic models 3,4 , it differs in its design focus on separating observable and non observable compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Predominantly, epidemiological models were used to predict the spread of the virus on a national and regional level. The models predicted the number of COVID-19 infections and hospital admissions, subsequently translated into bed requirements and deaths [28,22,10,31,24]. Additionally, epidemiological models were extended by incorporating lock-down measures and other non-pharmaceutical interventions to inform public policy [19].…”
Section: Pandemic Resource Prediction Modellingmentioning
confidence: 99%